Study on the relationship between buyer market power, spatial spillover effect, and profit in China's pharmaceutical industry - Guanyi, Yu; Lei, Wu; Heng, Chen; Zhengliang, Ding (Frontiers in Public Health, 2025)
Previous studies have extensively explored industrial innovation, but the impact of downstream buyer market power on upstream industries remains underexamined. Using a spatial Durbin model (SDM) and data from China's medical and pharmaceutical sectors (2001–2021), we analyze how buyer market power affects pharmaceutical industry profitability. Key findings include: (1) local buyer market power reduces local pharmaceutical profitability and may also negatively affect other regions through spatial spillover, though this spillover effect is weak. (2) Stronger regional economic ties amplify the impact of local medical industry power on pharmaceutical profitability. (3) Supplier countervailing power can mitigate the negative effects of buyer power on pharmaceutical profits. (4) Buyer market power significantly harms pharmaceutical profitability in western China and low capital-intensity sectors, but not in eastern or central regions and high capital-intensity sectors. (5) Asset specificity intensifies the negative impact of buyer power, while larger firm size helps reduce it. (6) Buyers can lower pharmaceutical profitability by reducing R&D investment. This study contributes to industrial organization theory by revealing how downstream buyer power affects upstream profitability. It expands empirical methods by incorporating spatial econometrics and offers policy suggestions for improving pharmaceutical industry performance from a vertical chain perspective.